1971
DOI: 10.1084/jem.133.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin and Renin in Rat and Dog Brain

Abstract: Since the discovery of the angiotensins a link was sought in vain between these polypeptides and the physiological mechanism that regulates the systemic blood pressure (1). This search, however, was rich in surprises as soon as the amazing diversity of pharmacological actions of angiotensin II was established. Besides being the most powerful vasopressor molecule known, the polypeptide is the hormone for aldosterone release (2) and has several effects on the autonomic nervous system: (a) it inhibits the uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(90 citation statements)
references
References 14 publications
1
87
0
2
Order By: Relevance
“…On the other hand, Hoffman and Phillips (18) reported that the most sensitive site of the hyper tensive effect of AT,, was the ventral anterior third ventricle or perivascular tissue sur rounding it and that the hypertensive effect was not apparent when AT,, was applied to the fourth ventricle. Although it has been reported that renin and angiotensin are endogenous (19,20) and that angiotensin in the dog brain is concentrated in the brainstem (19), this octapeptide is apparently not directly concerned with central vasomotor control mechanisms in the medulla, as in experiment, AT,, sensitive neurons showed no characteristic localization.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, Hoffman and Phillips (18) reported that the most sensitive site of the hyper tensive effect of AT,, was the ventral anterior third ventricle or perivascular tissue sur rounding it and that the hypertensive effect was not apparent when AT,, was applied to the fourth ventricle. Although it has been reported that renin and angiotensin are endogenous (19,20) and that angiotensin in the dog brain is concentrated in the brainstem (19), this octapeptide is apparently not directly concerned with central vasomotor control mechanisms in the medulla, as in experiment, AT,, sensitive neurons showed no characteristic localization.…”
Section: Discussionmentioning
confidence: 94%
“…The brain also has its own intrinsic reninangiotensin system from where Ang II is produced [25][26][27][28]. In rodents and humans, Ang II binding sites are expressed widely throughout the brain including the cerebral vasculature and circumventricular organs (CVO), where they have access to systemic Ang II [27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] By contrast, much less is known about the tissue RAS, and many questions about the angiotensin processing cascade and the role of the tissue RAS in regulating blood pressure and fluid balance remain unanswered. [4][5][6][7] Proangiotensin-12 (proang-12) is a 12-amino acid, C-terminal extended form of Ang I, which we recently isolated from rat small intestine. 8 In vitro, proang-12 constricts aortic strips and, when intravenously infused into rats, raises blood pressure.…”
Section: Introductionmentioning
confidence: 99%